Electrochemical Technologies As A Driver Of Automotive Decarbonization - Sharifov Eldor; Eshmirzayeva Mohinur; Rashidova Nilufar Tulkinovna (Stanford Database Library of American Journal of Applied Science and Technology, 2026)
Decarbonizing road transport requires replacing fossil carbon at the tailpipe while simultaneously reducing upstream emissions from energy supply chains and vehicle manufacturing. Electrochemical technologies—most prominently lithium-ion batteries, hydrogen fuel cells, and water electrolysers—form a connected technological ecosystem that enables this transition. Battery-electric powertrains directly convert electricity into motion with high efficiency, and their life-cycle climate benefit grows as electricity grids decarbonize. Hydrogen fuel-cell systems provide an alternative electrochemical route that can be particularly relevant where high utilization, fast refuelling, and long range are priorities, but their climate performance depends strongly on how hydrogen is produced. Meanwhile, electrolysis is the core electrochemical pathway for producing low-emissions hydrogen and a key enabler for coupling renewable electricity to mobility and industrial value chains. Beyond propulsion, electrochemical innovations in battery materials, manufacturing, diagnostics, and end-of-life recycling can cut the embedded emissions of vehicles and reduce dependence on high-impact primary mining. This IMRaD-structured article synthesizes current evidence on how electrochemical technologies drive automotive decarbonization across the full life cycle, identifies the principal constraints (critical materials, electricity and hydrogen carbon intensity, infrastructure, and recycling scale-up), and discusses engineering and policy levers that can accelerate net greenhouse-gas reductions.